2013
DOI: 10.1186/1471-2164-14-648
|View full text |Cite
|
Sign up to set email alerts
|

Combining in silico prediction and ribosome profiling in a genome-wide search for novel putatively coding sORFs

Abstract: BackgroundIt was long assumed that proteins are at least 100 amino acids (AAs) long. Moreover, the detection of short translation products (e.g. coded from small Open Reading Frames, sORFs) is very difficult as the short length makes it hard to distinguish true coding ORFs from ORFs occurring by chance. Nevertheless, over the past few years many such non-canonical genes (with ORFs < 100 AAs) have been discovered in different organisms like Arabidopsis thaliana, Saccharomyces cerevisiae, and Drosophila melanoga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
84
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 47 publications
0
84
0
1
Order By: Relevance
“…New translated regions have not only been identified in transcripts thought to be non-coding, but also upstream of a large fraction of protein-coding ORFs (so-called upstream ORFs, uORFs). 4,[13][14][15][16][17][18][19][20][21] These usually short translated ORFs were likely missed in previous mutagenesis screens due to their small size, and remained un-annotated in genome annotations due to their small size and lack of evidence for codingness. [22][23][24] In analogy to the term 'pervasive transcription', 25 this unforeseen prevalence of short ORF (sORF) translation has spurred the notion of 'pervasive translation'.…”
Section: Introductionmentioning
confidence: 99%
“…New translated regions have not only been identified in transcripts thought to be non-coding, but also upstream of a large fraction of protein-coding ORFs (so-called upstream ORFs, uORFs). 4,[13][14][15][16][17][18][19][20][21] These usually short translated ORFs were likely missed in previous mutagenesis screens due to their small size, and remained un-annotated in genome annotations due to their small size and lack of evidence for codingness. [22][23][24] In analogy to the term 'pervasive transcription', 25 this unforeseen prevalence of short ORF (sORF) translation has spurred the notion of 'pervasive translation'.…”
Section: Introductionmentioning
confidence: 99%
“…Translation inhibitors, such as harringtonine (HR), which generates a pile-up of RBFs at the start codon, have also been used to identify translation initiation sites in actively translated ORFs [30]. Some of these studies have focused exclusively on the identification of translated smORFs in fruit flies [32], zebrafish [31], yeast [36], and mice [41].…”
Section: Introductionmentioning
confidence: 99%
“…As demonstrated in Table 2 and Supplementary Table S2, the genome scanning revealed that the number of proteins in any of those studied 93 families predicted by SVM, PNN and KNN did not exceed 10% of the total number of proteins in the whole genome, and this was the same situation for the majority (82%) of the studied 93 families by BLAST. The higher number of proteins predicted for certain functional family may indicate a higher false discovery rate [113,114]. For human genome, the number of proteins identified by SVM was equivalent to or was slightly higher than that of both PNN and KNN, but was significantly lower than that of BLAST (Figure 2a).…”
Section: In-depth Assessment Of the False Discovery Rate By Genome Scmentioning
confidence: 98%
“…As reported, genome scanning was a comprehensive method to evaluate the capacity of protein functional prediction tools in identifying and classifying protein family [113,114]. In this paper, an evaluation on the false discovery rate of the studied protein function predictors was performed by scanning the genomes of 4 model organisms representing 4 species kingdoms (homo sapiens from Animalia, arabidopsis thaliana from Plantae, saccharomyces cerevisiae from Fungi and mycobacterium tuberculosis from Bacteria).…”
Section: Evaluating the False Discovery Rates Of The Studied Methodsmentioning
confidence: 99%
See 1 more Smart Citation